Enterprising and lost: Professional lives of programmer interns. (April 2021) - Wang, Chadwick; Yang, Kunyun
Programmer interns are a distinctive group of precarious laborers. They undertake the same jobs as junior programmers with formal employment, while suffering from high pressure and earning low pay. Still, they are convinced that only a long-term internship can keep them on the right track of professional career development. We explore their consent-making through six months of fieldwork in an internet company, and propose the "enterprising-self" game to explain their subjective orientations. In the enterprising-self game, programmer interns become accustomed to identifying themselves with a particular type of quantifiable labor product, for instance, the positioning of "their" sticky notes on company whiteboards and the expected "T-levels" that represent their employability in the industry, by which their enterprising self is a by-product. Programmer interns seems to believe that, rather than higher education, state-owned enterprises, or multinational enterprises, only domestic internet companies can help them attain their enterprising selves. Even though the supervisor–intern relationship and the "gender game" of masculinity performance constitute part of the programmer interns' enterprising-self game, the essence of the game has never been challenged and in some ways is only being reinforced. Though only a few lucky employees can win the game by attaining promotion to the senior engineer or management level, most of them still get lost in the "periodic" and "imperceptible" time of life as a programmer, which is characterized by full devotion to the company, until the "35-year-old crisis".